Characteristics and Management of Acid Soils Derived from Volcanic Rocks for Extensification of Maize in Sukabumi, West Java - DJADJA SUBARDJA (Jurnal Tanah dan Iklim (Indonesian Soil and Climate Journal), 2007)
Acid soils derived from volcanic rocks on wet climate of upland agriculture in the centre of maize production areas in Sukabumi, West Java are characterized by acid to strongly acid soil reaction (pH<5.5), low to very low base saturation, low to medium cation exchange capacity of clay, and medium to high aluminum saturation which could be a toxic and influencingphosphate availability. Composition of sand fraction indicates that parent material of soils was an intermediated volcanic rock, dominated by intermediated plagioclass i.e. andesine and labradorite, and mafic minerals of ferromagnesian i.e. hyperstene, hornblende, while clay fraction is dominated by type of 1:1 (halloysite and kaolinite). Generally, soils are deep, brown to reddish brown, clayey textured, crumb to fine sub angular blocky structured, friable, well drained, and moderatelly wellpermeability. Soils have an isohyperthermic temperature regime and udic soil moisture regime. Soils are classified as Brown Latosol and Reddish Brown Latosol or equal to Humic Dystrudepts and Typic Hapludults. Typic Hapludults much more developed and weathered than Humic Dystrudepts, therefore it has low fertility. Physically, soils are good medium for development of maize roots. But chemically are not suited for maize growth especially on Typic Hapludults. Therefore, they need specific soil management to improve soil productivity by increasing input of fertilizers, liming and organic matter based on soil characteristics and crop needs.